FAKTOR - FAKTOR YANG MEMPENGARUHI MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK ( Studi Empiris Pada Mahasiswa PTN Dan PTS Di Semarang) - Hindun Choiriyah, 12.05.52.0199; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of intrinsic value, financial rewards, professional training, professional recognition, social values, work environment, labor market considerations, personality, gender equality that directly affect accounting students in selecting a career as a public accountant. The population in this study is the force in 2012 accounting students at Universities and Colleges in Semarang. Sampling was done by using purposive sampling method and number of samples of 341 respondents. Primary data collection method used was a questionnaire method. Data were analyzed using multiple linear regression model. The results showed that the intrinsic value significant negative effect on the selection of a career as a public accountant, while the financial rewards and consideration of labor market positive effect is not significant to the selection of a career as a public accountant, and professional training, professional recognition, work environment, social values, personality and gender equality significant positive effect on the selection of a career as a public accountant.Keywords: Intrinsic Value, Financial Rewards, Professional Training, Professional Recognition, Social Values, Work Environment, Labor Market Considerations, Personality, Gender Equality, The Selection Of A Career As A Public Accountant